2022
DOI: 10.18632/aging.204410
|View full text |Cite
|
Sign up to set email alerts
|

JAK2/STAT3 pathway mediates neuroprotective and pro-angiogenic treatment effects of adult human neural stem cells in middle cerebral artery occlusion stroke animal models

Abstract: Mismatches between pre-clinical and clinical results of stem cell therapeutics for ischemic stroke limit their clinical applicability. To overcome these discrepancies, precise planning of pre-clinical experiments that can be translated to clinical trials and the scientific elucidation of treatment mechanisms is important. In this study, adult human neural stem cells (ahNSCs) derived from temporal lobe surgical samples were used (to avoid ethical and safety issues), and their therapeutic effects on ischemic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Many studies have widely confirmed that inhibition of STAT3 phosphorylation using genetic or pharmacologic approaches could significantly improve neurological outcomes in cerebral ischemic models, [ 24 , 25 ] raising hopes for new therapeutic modalities of stroke. [ 26 , 27 ] Recent studies have also explored the therapeutic effects of several direct or indirect p-STAT3 inhibitors in rodent models of acute brain injury. [ 28 , 29 ] Zhu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have widely confirmed that inhibition of STAT3 phosphorylation using genetic or pharmacologic approaches could significantly improve neurological outcomes in cerebral ischemic models, [ 24 , 25 ] raising hopes for new therapeutic modalities of stroke. [ 26 , 27 ] Recent studies have also explored the therapeutic effects of several direct or indirect p-STAT3 inhibitors in rodent models of acute brain injury. [ 28 , 29 ] Zhu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Transplanting exogenous stem cells into the brain can fill the shortage of endogenous NSCs and stimulate nerve regeneration, rebuilding or repairing the brain-damaged area’s neural network. 52 Secondly, the paracrine effect can be observed in the context of stem cell transplantation in the brain.…”
Section: How Effective Is Neural Stem Cell Therapy For Ischemic Strokementioning
confidence: 99%
“…Recent studies have focused on different types of stem cells including MSCs, neural stem cells (NSCs), and hair follicle stem cells. Among these, MSCs have been extensively investigated in preclinical and clinical research due to their capacity to mitigate oxidative stress, produce cytokines and extracellular vesicles that inhibit proinflammatory cytokines and inflammatory cell activation, suppress pyroptosis, as well as reduce BBB permeability [74]. Ha et al [75] verified that adult human NSCs can significantly reduce tissue and neural function loss, which is mediated through its paracrine neuroprotective and proangiogenic activities through the Janus kinase 2/signal transducer and activator of transcription 3 (JAK2/STAT3) signaling pathway.…”
Section: Stem Cellsmentioning
confidence: 99%